Promoting the use of probabilistic weather forecasts through a dialogue between scientists, developers and end‐users. (16th April 2019) - Fundel, Vanessa J.; Fleischhut, Nadine; Herzog, Stefan M.; Göber, Martin; Hagedorn, Renate
Abstract : Today's ensemble weather prediction systems provide reliable and sharp probabilistic forecasts—yet they are still rarely communicated to outside users because of two main worries: the difficulty of communicating probabilities to lay audiences and their presumed reluctance to use probabilistic forecasts. To bridge the gap between the forecasts available and their use in day‐to‐day decision making, we encourage scientists, developers, and end‐users to engage in interdisciplinary collaborations. Here, we discuss our experience with three different approaches of introducing probabilistic forecasts to different user groups and the theoretical and practical challenges that emerged. The approaches range from quantitative analyses of users' revealed preferences online to a participatory developer–user dialogue based on trial cases and interactive demonstration tools. The examples illustrate three key points. First, to make informed decisions, users need access to probabilistic forecasts. Second, forecast uncertainty can be understood if its visual representations follow validated best practices from risk communication and information design; we highlight five important recommendations from that literature for communicating probabilistic forecasts. Third, to appreciate the value of probabilistic forecasts for their decisions, users need the opportunity to experience them in their everyday practice. With these insights and practical pointers, we hope to support future efforts to integrate probabilistic forecasts into everyday decision making. Abstract : Ensemble predictions provide reliable and sharp probabilistic forecasts, yet these are still rarely communicated to end‐users. We present three approaches to introducing probabilistic weather forecasts – and illustrate three key insights: (a) to make informed decisions, users need probabilistic forecasts; (b) users can understand forecast uncertainty if representations follow best practices from risk communication; and (c) users need to experience probabilistic forecasts in their day‐to‐day practice to evaluate their benefit. With these insights and practical pointers, we hope to support future efforts to integrate probabilistic forecasts into everyday decision making and to encourage everyone to seek interdisciplinary collaborations.